The impact of taxes on competition for CEOs - Peter Krenn (Arbeitskreis Quantitative Steuerlehre (arqus), 2015)
This paper tries to answer the question how taxation of corporate and individual income affects competition among firms for highly-skilled human resources like CEOs. It shows that individual income taxes can perform a substantial impact on the outcome of such a competition if marginal tax rates are different like in an international labor market. Additionally, it presents the surprising result that in a local labor market for CEOs observed gross fixed salaries should decline in the individual income tax rate. The effects of taxation in a market for CEOs is in particular an interesting topic because recent developments with respect to compensation practices of top-level managers have opened a public debate about the use of instruments for regulating compensation of those managers. The investigation follows an analytical economics-based approach by extending an LEN type model of moral hazard with elements of competition and income taxation. It investigates the impact of differential taxation on the competition between two firms for the exclusive service of a unique, highly-skilled CEO.
Keywords: D82; H24; H25; J31; J33; L13; 330; CEO; taxes; competition for talents; skilled human resources